HUBUNGAN POLA ASUH ORANG TUA TERHADAP PERKEMBANGAN MORAL ANAK USIA DINI DI ERA DIGITAL - Indah Dwi Rahmawati; Eko Setiawan; Ika Anggraheni (UNISMA, 2022)
The existence of technological developments that are increasingly developing can cause changes in values, norms, rules, and morals of life adopted by society, or what is called moral degradation. All platforms can be accessed by all people, from adults to early childhood. Moral education needs to be introduced to children from an early age as an effort to form a generation that is spiritually strong and polite in terms of morals.or parenting style is one of the factors that significantly help shape the morals or character of children. This is based on the fact that family education is the primary and first education for children that cannot be replaced by any educational institution. However, what is happening at this time is that most parents have not implemented good parenting for their children in accordance with the needs and development of children. This study aims to describe the moral development of early childhood in the digital era and to describe the relationship of parenting patterns to the moral development of early childhood in the digital era in grade A and B students of TA Al Kautsar Malang in the 2021/2022 academic year. The research method used in this study is a quantitative correlation method. The subjects of this study were students of class A and B of TA Al Kautsar Malang in the 2021/2022 academic year with a total of 57 students and 57 parents. The results of the analysis state that the moral development of early childhood is based on three factors, namely psychological factors, factors of good behavior and bad behavior and there is a significant relationship between parenting patterns and the moral development of early childhood in the digital era.